Ecofeminism in Resistance: Women and Indigenous Peoples Against Coal Mine Hauling on the Border of East Kalimantan and South Kalimantan - Safaranita Nur Effendi; Niken Nurmiyati; Rizki Anggarini Santika Febriani (Dealings Foundation Institute, 2025)
This research examines the exploration of ecofeminism in the resistance of women in Batu Kajang Village and indigenous people in Muara Kate Komam against the hauling activities of PT Mantimin Coal Mining (MCM). This resistance was triggered by Batu Kajang women's concerns about the potential negative impacts of hauling, such as threats to children's safety, infrastructure damage, and increased ecological damage. The initial phase of this resistance was marked by local women's establishment of guard posts, aiming to safeguard the surrounding environment. Subsequently, the indigenous people of Muara Kate reinforced the border guard of East Kalimantan and South Kalimantan in response to the growing number of casualties resulting from the hauling activities of the company above. This research employs a qualitative approach, incorporating a phenomenological analysis and drawing upon event documentation, articles, news, journals, books, and in-depth interviews. The results suggest that ecofeminism is gaining traction as a significant motivating factor in the resistance to coal mining. Indigenous women play a pivotal role in integrating environmental concerns with their efforts to defend their social and cultural rights, which are inextricably linked to their customary lands. These communal lands hold immense economic, social, and cultural value for indigenous communities, and their destruction poses a serious threat to their survival. It is recommended that the government consider ways to support Indigenous women, such as by creating opportunities for their involvement in decision-making processes and ensuring the protection of their rights through responsive and equitable policies. The recognition of Indigenous women's role in this resistance and support from the government could contribute to strengthening efforts to protect their environment and cultural sustainability.